A critical comparative review of evidence on alternative instruments for supporting research and innovation in agri-food systems in the Global South - Letty, Brigid Aileen; Hart, Tim G. B.; Murugan, Simone; Naidoo, Theolin; Rai, Sharad; Thiam, Djibril; Zake, Joshua; Sershen,; Annor-Frempong, Irene (Frontiers in Sustainable Food Systems, 2022)
Financial support is a critical enabling factor for healthy agri-food innovation systems, particularly within resource-limited settings, though additional forms of support are also necessary. This motivated a critical comparative review of evidence in peer-reviewed and grey literature on the range of instruments that support innovation in agri-food systems in the Global South, toward achieving sustainable agriculture intensification. The main aim is to provide recommendations to innovation managers on the choice of different instruments for supporting innovation. The key guiding questions for the comparative analysis were whether the instrument fosters uptake of innovation and whether it promotes inclusive development. A review of the literature was supplemented with a scan of websites for sources of peer-reviewed and grey literature documenting the application of the 12 selected instruments. The study revealed three categories of instruments: (Type A) those that support entrepreneurship; (Type B) those that primarily finance innovation; and (Type C) those that support innovation in real-life contexts. Our analysis indicates that innovation managers and funders need to select instruments that are likely to fit the specific context as well as to address the mandates of their organizations, and in so doing, they must consider how to ensure the sustainability of their investments and meet the needs of their beneficiaries. This review represents one of a handful that have compared the use of multiple instruments across multiple continents in the Global South, and can serve as an important decision-making tool for investors and funders looking to invest in agri-food innovation systems.